Enhancing Spontaneous Arabic Speaking through Task-Based Interaction: A Classroom Study at an Islamic University - Abdurrahman Ahmad Aqil (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Spontaneous Arabic speaking remains a major challenge for university students because many learners can understand grammatical rules and memorize dialogues but still hesitate to produce Arabic orally in unscripted interaction. This study aims to examine how task-based interaction enhances spontaneous Arabic speaking among students at Universitas Islam Internasional Darullughah Wadda’wah. Using a mixed-method classroom intervention design, the study involved 30 undergraduate students of Arabic language education. Quantitative data were collected through pre-test and post-test speaking assessments, while qualitative data were obtained from classroom observation, field notes, and semi-structured interviews. The findings showed that students’ mean speaking score increased from 60.60 to 78.90, with significant improvement in fluency, vocabulary use, pronunciation, accuracy, and especially interactional responsiveness. The paired-sample t-test also indicated a significant difference, t(29) = 13.42, p < .001, with a large effect size. Qualitative findings revealed that task-based interaction reduced dependence on memorized dialogues, increased confidence, activated vocabulary more quickly, and encouraged meaningful peer communication. The study contributes analytically by positioning spontaneous Arabic speaking as a specific dimension of mahārah al-kalām, particularly through immediate response, turn-taking, repair strategies, and interactional courage